Types and Tools Available for Fluency Disorder –Speech Therapy (International Journal of Engineering and Computer Science, 2015)
Automatic Speech Recognition (ASR) is the process by which a machine is able to recognize and act upon spoken language or utterances. Speech recognition discipline is a system within sound technologies that tries to gain a seat in the course of advancing technology. Fluency disorder is an interruption in the flow of speaking characterized by a typical rate, rhythm, and repetitions in sounds, syllables, words, and phrases. Artificial recognition and disfluency identification are considered to be complicated in fluency disorders. The fluency disorder which is mainly focused in this paper is stuttering which is characterized by various behaviors that interface with the forward flow of speech. While all individuals are disfluent to some extent, on the surface and differentiate stutterers from non stutterers are the frequency of their disfluency and/or the cruelty of their disfluency. In young children, typical nonfluent speech is initially episodic, and then becomes more cyclical in nature, coming and going without apparent cause or pattern. This paper presents the types of stuttering, stuttering therapy, techniques used for stuttering therapy and mainly focus on the young children.